2022
DOI: 10.1155/2022/5108389
|View full text |Cite
|
Sign up to set email alerts
|

Radial Artery Calcification in Predicting Coronary Calcification and Atherosclerosis Burden

Abstract: Background. Atherosclerosis is a systemic arterial disease with heterogeneous involvement in all vascular beds; however, studies examining the relationship between coronary and radial artery calcification are lacking. The purpose of this study was to assess the relationship between the two sites and the prognostic value of radial artery calcification (RC) for coronary artery disease. Methods. This is a single-center, retrospective cross-sectional study based on Doppler ultrasound of radial artery (RUS) and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…Plaque formation, calcinosis, reduced lumen, or occlusion are accessible for diagnosis ( Figure 6 , panel C). A recent study found a significant correlation between radial calcification and coronary calcification; therefore, US may even play a key role in predicting severe coronary artery disease [ 25 ]. Moreover, the multivariable logistic regression found a strong correlation between risk factors such as age, smoking, chronic kidney disease, and diabetes mellitus and radial artery calcification [ 25 ].…”
Section: Benefits Learning Curve Different Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Plaque formation, calcinosis, reduced lumen, or occlusion are accessible for diagnosis ( Figure 6 , panel C). A recent study found a significant correlation between radial calcification and coronary calcification; therefore, US may even play a key role in predicting severe coronary artery disease [ 25 ]. Moreover, the multivariable logistic regression found a strong correlation between risk factors such as age, smoking, chronic kidney disease, and diabetes mellitus and radial artery calcification [ 25 ].…”
Section: Benefits Learning Curve Different Scenariosmentioning
confidence: 99%
“…A recent study found a significant correlation between radial calcification and coronary calcification; therefore, US may even play a key role in predicting severe coronary artery disease [ 25 ]. Moreover, the multivariable logistic regression found a strong correlation between risk factors such as age, smoking, chronic kidney disease, and diabetes mellitus and radial artery calcification [ 25 ]. This helps to understand how metabolic systemic diseases affect even the far end of the arterial tree [ 26 , 27 ].…”
Section: Benefits Learning Curve Different Scenariosmentioning
confidence: 99%
“…The phenotypic manifestations of atherosclerosis vary in each individual and throughout the body; it is not fully understood why plaque formation has such a heterogeneous distribution, although different arterial systems are correlated [ 1 , 2 , 3 ]. Moreover, risk factors (such as diabetes mellitus, hypertension, smoking, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the small sample size in our study, an effect may not be excluded with certainty. A recent study by Achim et al revealed a further interesting aspect, demonstrating that radial artery calcification is correlated with coronary calcification and plaque burden requiring revascularization [ 24 ]. This suggests that radial ultrasound may also be useful for preoperatively identifying patients with significant coronary atherosclerosis, underlining the role of the anesthesiologist in screening for relevant comorbidities.…”
Section: Discussionmentioning
confidence: 99%